Educational Planning and Human Resource Management: A Study of Public and Private Schools in Pakistan - Adeela Rehman (Journal of Education and Vocational Research, 2019)
Planning and management of curriculum and human resources in schools is precisely liable and precarious in nature. The present study addressed the matter while exploring the practices of educational planning and human resource management in public and private primary level schools in Punjab, Pakistan. The case studies of two public and private schools in Rawalpindi District of Punjab Province were conducted by interviewing the mangers and principles of private and public school respectively. The participant observations were also taken to substantiate the information provided by the respondents. The schools were selected on the basis of their reputation and high enrollment of the students. The findings of the study elaborated the differences in public and private schools with respect to educational planning and managing human resource. The public schools followed the standard curriculum designed by the Punjab text book board which is universal for all the public schools. The teachers are mostly on permanent position and experienced. Whereas in the private schools, international level curriculum is followed this differs from school to school. Every private school has their own curriculum which they followed according to the standard of the school. The manager of the school generally decides the nature of the curriculum and recruitment of the teacher on its own will and interests. The medium of instruction is English in private schools, while public school used both national and international language. As far as teacher competence is concern, the public school teachers are more experienced as compare to private schools as they are working at the same school for a longer time period due to which better able to manage various task in the school and also take part in educational planning. On the other hand, in private school, fresh and most of the time untrained young females are hired. For these employees, professional development and retention is very important for the managers. Selecting and recruiting new teacher is very tedious job as well as it also affects the student’s performances and achievements. It is indicated that the owner of the private school was in continues struggle and in apprehension of hiring, and retaining their staff by providing them extra bonuses and facilities at school, such as leaves, time flexibility, and reward etc.